Single Crystal to Single Crystal (SC‐to‐SC) Transformation from a Nonporous to Porous Metal–Organic Framework and Its Application Potential in Gas Adsorption and Suzuki Coupling Reaction through Postmodification. Issue 15 (3rd March 2015) - Sen, Rupam; Saha, Debraj; Koner, Subratanath; Brandão, Paula; Lin, Zhi
Abstract A new amino‐functionalized strontium–carboxylate‐based metal–organic framework (MOF) has been synthesized that undergoes single crystal to single crystal (SC‐to‐SC) transformation upon desolvation. Both structures have been characterized by single‐crystal X‐ray analysis. The desolvated structure shows an interesting 3D porous structure with pendent NH2 groups inside the pore wall, whereas the solvated compound possesses a nonporous structure with DMF molecules on the metal centers. The amino group was postmodified through Schiff base condensation by pyridine‐2‐carboxaldehyde and palladium was anchored on that site. The modified framework has been utilized for the Suzuki cross‐coupling reaction. The compound shows high activity towards the CC cross‐coupling reaction with good yields and turnover frequencies. Gas adsorption studies showed that the desolvated compound had permanent porosity and was microporous in nature with a BET surface area of 2052 m2 g−1. The material also possesses good CO2 (8 wt %) and H2 (1.87 wt %) adsorption capabilities.